한국형 건강정보이해능력 측정도구(Korean Health Literacy Assessment Tool)의 비교 및 개선 방안 - 이수현(Su Hyun Lee); 최은혜라(Eun Hye Ra Choi); 제민지(Min Ji Je); 한흥식(Heung Sik Han); 박병규(Byung Kyu Park); 김성수(Sung Soo Kim) (保健敎育健康增進學會誌, 2011)
Objectives: The purpose of the study is 1) to improve the previously developed KHLAT(Korean Health Literacy Assessment Tool) by testing two versions of KHLAT and 2) to develop guidelines to the grade range for KHLAT. Methods: The two versions of KHLAT(2) KHLAT(4) were administered to students from 1st grade to 12th grade in Busan. Data on 2673 participants were analyzed. Comparisons were made according to the grade range in REALM and the Korean grade range. Results: Both versions showed the increase of scores as the grade level increases. Female scored higher than male. However, the mean score (39.16) of KHLAT(2) was higher than that (29.6) of KHLAT(4). This result might be due to more specified responses of KHLAT(4). This difference was more clearly shown when the REALM grade range and Korean grade range were compared. The mean scores of KHLAT were lower than the means scores of the REALM in USA. Conclusions: The guidelines which were based on Korean school grad range were more suitable for Koreans.